Effect of regional block technique on postoperative high-grade complications according to Clavien-Dindo classification in elderly patients with thoracic and abdominal cancer: a retrospective propensity score matching analysis - Ding, Weisi; Zhang, Yunpeng; Liu, Huixin; Zhou, Tianxin; Zhao, Wanlu; Feng, Yi; An, Haiyan (Frontiers in Oncology, 2023)
Background: Postoperative complications have an influence on postoperative rehabilitation, length of hospital stay and hospitalization expenses in elderly patients, especially those with higher Clavien-Dindo (C-D) classification. Patients with cancers often experience more serious postoperative complications after surgery. Different anesthesia methods can affect the postoperative outcomes of cancer patients. Regional block techniques have been recommended in guidelines for enhanced recovery after surgery. However, the relationship between regional blocks and high Gradehigh-grade postoperative complications remains unclear, thus, the study explored the relationship between regional block techniques and high Gradehigh-grade postoperative complications graded by Clavien-Dindo classification in elderly patients with thoracic and abdominal cancer.